Switched at birth. Volume one [videorecording (DVD)] - Weiss, Lizzy (2011)
Bay Kennish, who grew up in a wealthy family with happily married parents and an older brother, and Daphne Vasquez, who lost her hearing as a child and grew up with a single mother in a working-class neighborhood, find their lives turned upside down when they discover they were accidentally switched at birth.